Krize - čas očisty a změny - Brychtová, Šárka (Univerzita Pardubice, 2009)
Submitted article is attempt about uneconomic look on present-day economic crisis. Text tries affects of the substance of the crisis in its wider connections and creates parallel between crisis in common force and the economic crisis. It comprehends this crisis like an illness and it indicates possible solution in future. The article shelters in them philosophical hidden meaning.
Keywords: economical crisis; crisis like an illness; causes of crisis; way from crisis; balance